Novel rechargeable nanostructured calcium phosphate crown cement with long-term ion release and antibacterial activity to suppress saliva microcosm biofilms. (July 2022) - AlSahafi, Rashed; Mitwalli, Heba; Alhussein, Abdullah; Melo, Mary Anne S.; Martinho, Frederico; Lynch, Christopher D.; Oates, Thomas W.; Xu, Hockin H.K.; Weir, Michael D.
Abstract: Objective: Resin cements with remineralizing and antibacterial properties are favorable for inhibition of caries. The objectives of this study were: (1) to investigate the capability of the novel dimethylaminohexadecyl-methacrylate (DMAHDM) and nano-sized amorphous calcium phosphate (NACP) containing cement to reduce saliva microcosm biofilm, and (2) to investigate the long-term ion release, recharge, and re-release of DMAHDM-NACP cement. Methods: Pyromellitic glycerol dimethacrylate (PMGDM) and ethoxylated bisphenol-A-dimethacrylate (EBPADMA) were used to make PEHB monomer . Five cements were fabricated: (1) PEHB+0%NACP+0%DMAHDM (experimental control); (2) PEHB+25%NACP+0%DMAHDM, (3) PEHB+25%NACP+0%DMAHDM; (4) PEHB+25%NACP+3%DMAHDM; (5) PEHB+25%NACP+5%DMAHDM. RelyX luting cement was used as commercial control. Colony-forming units (CFU), lactic acid production, metabolic activities, and minimum inhibitory concentration (MIC) were performed. Long-term Calcium (Ca) and phosphate (P) ion release, recharge, and re-release were assessed. Results: Compared to experimental and commercial controls, the NACP-DMAHDM cement significantly reduced CFU biofilm by 2–3 orders of magnitude, metabolic activities from 0.24±0.06 A540 /cm 2 to 0.03±0.01 A540 /cm 2, and lactic acid production from 27.7 ± 2.5 mmol/L to 5.4 ± 2.1 mmol/L ( n = 6) ( p <0.05). The DMAHDM showed an MIC value of 0.03 mg/L. However, when the DMAHDM was combined with PMGDM monomer, the MIC was greater than DMAHDM alone. The ion concentrations for the experimental groups significantly increased over time (1–84 days), indicating continuous ion release ( n = 3) ( p <0.05). Increasing the DMAHDM mass fraction from 0% to 5% and 3% to 5% significantly enhanced ion recharge and re-release at the third cycle ( p <0.05). Conclusions: Incorporating DMAHDM and NACP into resin-based crown cement provides strong antibacterial action against saliva microcosm biofilm and presents a high level of Ca and P ion recharge abilities, exhibiting long-term Ca and P ion release and remineralization potential. Clinical Significance: Resin based cement containing NACP and DMAHDM were developed with remineralizing and potent antibacterial effects. This cement formulation showed ion release and remineralization potential and are promising formulations to inhibit the incidence of recurrent caries and could promote remineralization and be sustainable for the long term. Graphical abstract: Image, graphical abstract